Environmental challenges in outer space in the framework of the second space age (Journal of the Spanish Institute for Strategic Studies, 2018)
The second space age (1991-present) is distinguished by two characteristics:the difficulty in reaching space governance agreements withemerging geopolitical actors, unlike the first space age (1957-1990) duringwhich the entire space regulatory framework was structured; andthe advent of numerous new public and private space actors –especiallyfrom 2010 onwards– triggering a corresponding increase in space activitiesin order to benefit from space applications such as reconnaissanceactivities, communications, space positioning systems and meteorology.These two factors are directly affecting the fragile space environment,and placing its sustainability at risk. In the absence of an internationalregulatory framework, the adoption of national laws is presented hereas an alternative means of ensuring the responsible management of thespace environment.